Current status of recombinant duck enteritis virus vector vaccine research - Jia, Wen-Feng; Wang, An-Ping; Wu, Zhi; Lei, Xin-Nuo; Cheng, Yu-Ting; Zhu, Shan-Yuan (Frontiers in Veterinary Science, 2025)
Duck enteritis virus (DEV), the pathogen of duck viral enteritis, belongs to the α-herpesvirus subfamily. Like other herpesviruses, it has a large genome with multiple non-coding and non-essential regions for viral replication. It is suitable as a live virus vector for inserting and expressing antigenic genes from other pathogens to develop multivalent vaccines. With the advancement of molecular biology research and experimental technology, genetic modification of the DEV genome has matured, leading to the successful construction of recombinant DEV live vector vaccines. These vaccines have demonstrated the ability to resist DEV and other pathogens, showing potential as recombinant viral vaccine vectors and playing a crucial role in the development of new avian vaccines. This article provides an overview of the progress of research on recombinant vaccines using DEV as the vector. It includes the biological characteristics of DEV and its advantages and limitations as a vaccine vector, methods for constructing recombinant DEV, the technical platform for efficiently building recombinant DEV, factors affecting the immune protection efficacy of recombinant DEV, and the application of recombinant DEV in vaccine development. Aiming to provide a reference for the development of duck enteritis virus vector-based vaccines.